Faktor-Faktor yang Memengaruhi Audit Delay pada Perusahaan Indeks LQ45 yang Terdaftar di Bursa Efek Indonesia - Raja Vanaldo Boang Manalu; Indah Setyaning Hastuti (Universitas Muhadi Setiabudi, 2023)
Audit delay is the time span required by an auditor in completing the audit process on a company's financial statements. Audit delay occurs when there are obstacles or obstacles in carrying out the audit that can affect the audit completion time. There are several factors that affect audit delay, such as company size, reputation of the Public Accounting Firm (KAP), auditor opinion and profitability. The population in this study were companies incorporated in the LQ45 index listed on the IDX for the 2019-2022 period, and a sample of 11 companies was taken with purposive sampling. The statistical method used is multiple linear regression analysis. The results showed that company size has a significant positive effect on audit delay. KAP reputation has no significant negative effect on audit delay. Auditor opinion has no significant negative effect on audit delay. Profitability proxied by Return on Assets has a significant positive effect on audit delay. Simultaneously proving that company size, KAP reputation, auditor opinion and profitability (ROA) together have a significant effect on audit delay.